Potential Mechanisms to Explain the Increased Levels of Beta-Endorphin during Exercise - Jamurtas, Αθανάσιος Ζ. (Inquiries in Physical Education and Sport, 2010)
Beta endorphin (β-ΕΝ) is a 31 aminoacid neuropeptide that is classified as an endogenous opioid, a peptide whose properties are to some degree opium- or morphine-like. β-EN is secreted as part of a larger precursor molecule (pro-opiomelanocortin). Smoking, alcohol intake and exercise are some factors that affect the blood levels of β-ΕΝ. The intensity and duration of exercise are determinant factors for elevated levels of β-ΕΝ during exercise. The proposed mechanisms to explain the increased levels of β-ΕΝ with exercise include analgesia, lactate, acid-base balance and metabolic regulation.